An Optical-Fiber-Based Smart Textile (Smart Socks) to Manage Biomechanical Risk Factors Associated With Diabetic Foot Amputation. (July 2017) - Najafi, Bijan; Mohseni, Hooman; Grewal, Gurtej S.; Talal, Talal K.; Menzies, Robert A.; Armstrong, David G.
Objective: This study aimed to validate a smart-textile based on fiber-optics for simultaneous measurement of plantar temperature, pressure, and joint angles in patients with diabetic peripheral neuropathy (DPN). Methods: After in-vitro validation in the laboratory, 33 eligible subjects with DPN were recruited (age: 58 ± 8 years, BMI: 31.5 ± 8 kg/m 2 ) for assessing plantar pressure and temperature during habitual gait-speed in a clinical-setting. All participants were asked to walk at their habitual speed while wearing a pair of sensorized socks made from highly flexible fiber optics (SmartSox). An algorithm was designed to estimate temperature, pressure, and toe range of motion from optical wavelength generated from SmartSox. To validate the device, results from thermal stress response (TSR) using thermography and peak pressure measured by computerized pressure insoles (F-Scan) were used as gold standards. Results: In laboratory and under controlled conditions, the agreements for parameters of interest were excellent ( r > .98, P = .000), and no noticeable cross-talks between measurements of temperature, angle, and pressure were observed. During clinical data acquisition, a significant correlation was found for pressure profile under different anatomical regions of interest between SmartSox and F-Scan ( r = .67, P < .050) as well as between thermography and SmartSox ( r = .55, P < .050). Conclusion: This study demonstrates the validity of an innovative smart textile for assessing simultaneously the key parameters associated with risk of foot ulcers in patients with DPN. It may empower clinicians to objectively stratify foot risk and provide timely care. Another study is warranted to validate its clinical application in preventing limb threating problems in patients with DPN.